Implementasi Contextual Teaching and Learning dalam Mengoptimalkan Pembelajaran Fikih pada Siswa Madrasah Tsanawiyah (MTs) - Luli Huliyah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This study is motivated by the continued dominance of lecture-based and drill methods in Fiqh learning, which results in low student interest and enthusiasm. This contradicts the demands of the 2013 Curriculum, which emphasizes student activeness and critical thinking. Therefore, a more effective and efficient learning model is needed. The purpose of this study is to describe the implementation of the Contextual Teaching and Learning (CTL) model in improving students' understanding of Fiqh material at MTs Nurul Hidayah. This research uses a descriptive method with a qualitative approach. Data were collected through interviews, observations, and documentation. The results of the study indicate that the implementation of the CTL model has been quite effective. This can be seen from the active involvement of students in the learning process through activities such as observing, discussing, working in groups, and connecting the material with real-life experiences. Learning through the CTL approach makes the process more meaningful and contextual, enabling students to gain a deeper and longer-lasting understanding of the Fiqh material.